DESKRIPSI PEMBELAJARAN MENULIS PUISI SISA KELAS V SEKOLAH DASAR NEGERI 52 SINGKUT BULUH - Roly, Florensius; Halidjah, Siti; Pranata, Rio (Universitas Tanjungpura, 2023)
This study aims to describe language errors in the text written by students describing learning to write poetry in class V SDN 52 Singkut Buluh. The research method used is a descriptive method with a qualitative research form. The source of the data for this research is the fifth grade teacher at the 52 Singkut Buluh State Elementary School. The data of this research are the results of interviews about the implementation of poetry writing learning. The results of the analysis show that the teacher-made lesson plans are assessed sequentially, assessed from the formulation of learning objectives to the assessment of learning outcomes. The learning objectives contained in the lesson plan are that students can write free poetry by using the appropriate choice of words. The learning objectives are appropriate, which are guided by competency standards, namely expressing thoughts and feelings in free poetry. The basic competence is to write free poetry by using the appropriate choice of words. The learning objectives are consistent with the indicators provided in the competency standards and basic competencies, ensuring that the indicators and learning objectives are consistent with the stipulations in the Learning Implementation Plan. The way to solve the problem of learning to write poetry is with the ASTUTI learning model (observe, select, find, try, add and tie).